Efficacy of dietary interventions in individuals with substance use disorders for illicit substances or illicit use of pharmaceutical substances: A systematic review. Issue 6 (2nd March 2021) - Whatnall, Megan C.; Skinner, Janelle; Pursey, Kirrilly; Brain, Katherine; Collins, Rebecca; Hutchesson, Melinda J.; Burrows, Tracy L.
Abstract: Background: Disordered eating habits, poor dietary intake and nutritional status, and altered body composition are highly prevalent among individuals with substance use disorders. This systematic review aimed to evaluate the efficacy of dietary interventions in adults with substance use disorders for illicit substances or illicit use of pharmaceutical substances. Methods: Eight scientific databases were searched using predetermined text word and subject heading (MeSH) searches for experimental studies published up to March 2020 that evaluated interventions aiming to improve dietary intake in adults with substance use disorders for illicit substances or illicit use of pharmaceutical substances, which included dietary intake outcomes. Results: Of 9299 articles identified, five studies were included. Three studies (60%) were conducted in outpatient/community clinic settings and two studies (40%) were conducted in inpatient/residential treatment centres. Dietary interventions ranged in duration from 5 weeks to 24 months. These included education and behaviour change advice for nutrition and other lifestyle behaviours ( n = 3 studies), nutrition education and provision of healthy food choices within the residential treatment centre ( n = 1 study), and polyunsaturated fatty acid supplementation ( n = 1 study). Three studies (60%) reported small but significant change in one or more dietary outcome at post‐intervention, including reductions in sweets, fast food or caffeine intake, as well as increases in fruit and vegetable intake. Conclusions: This review has identified a small number of studies, despite the strong evidence that dietary intervention is needed in substance use rehabilitation. More research is needed to determine the most effective intervention approaches for this group, including robust study designs. Abstract : Disordered eating habits, poor dietary intake and nutritional status, and altered body composition are highly prevalent among individuals with substance use disorders. This systematic review of dietary interventions in adults with substance use disorders for illicit substances or illicit use of pharmaceutical substances identified only five studies, demonstrating that there is limited evidence in this area.